NOTES ON PHYLLOCNISTIS SP., CHIRIMOYO FOLIAGE MINER - SANABRIA DE ARÉVALO, ISABEL (Revista Colombiana de Entomología, 1982)
The moth Phyllocnistis sp. (Lepidoptera: Gracillariidae) is a common pest of chirimoyo (Annona cherimolia Mill) in different regions of Colombia, especially in the stages of Boyacá and Cundinamarca. The larva of this insect mines the upper side of the leaves and may cause severe damage. Up to 85o/o of the leaves can be found with damage to the leafminer. A leaf may support up to eight larvae in different stages of development. The eggs, larvae, pupae, and adults of this insect are described in this work.